”I virkeligheden er det jo ikke tiggeriet, der er det store problem”: Stranger-danger-diskurs i en dansk kontekst - Petersen, Emilie Willads (Journal of Language Works - Sprogvidenskabeligt Studentertidsskrift, 2022)
This study investigates how the stranger danger discourse as described by Ahmed (2000) can be understood in a Danish context. It asks the questions of how fear as a phenomenon occurs during legislative processes and how it affects the social identities ascribed to the participants involved in the process. These questions are examined through a critical discourse analysis of the legislative process of an anti-begging law that was passed by the Danish Parliament in 2017. The analysis shows that the identification of participants is primarily based on either the presence or absence of the categories ‘dwelling’ and ‘Danishness’. Activation of the two categories form a social hierarchy through which the participant in the lowest position, in this case foreign homeless people, are recognized as strangers. The study concludes that the presence of people recognized as strangers in a Danish societal context becomes an image of the end of the Welfare State, and in order to keep status quo it leads to a wish of disposal of the deviating element. In this way the anti-begging law and the legislative process around it becomes an illustrative example of how the stranger danger discourse can be (re)produced on a political level.